Generation and Analysis of 25 Mb of Genomic DNA from the Pufferfish Fugu rubripes by Sequence Scanning - Elgar, Greg; Clark, Melody S.; Meek, Stephen; Smith, Sarah; Warner, Sarah; Edwards, Yvonne J.K.; Bouchireb, Nassima; Cottage, Amanda; Yeo, Giles S.H.; Umrania, Yagnesh; Williams, Gary; Brenner, Sydney (Genome Research, 1999)
We have generated and analyzed >50,000 shotgun clones from 1059Fugu cosmid clones. All sequences have been minimally edited and searched against protein and DNA databases. These data are all displayed on a searchable, publicly available web site athttp://fugu.hgmp.mrc.ac.uk/. With an average of 50 reads per cosmid, this is virtually nonredundant sequence skimming, covering 30%–50% of each clone. This essentially random data set covers nearly 25 Mb (>6%) of the Fugu genome and forms the basis of a series of whole genome analyses which address questions regarding gene density and distribution in the Fugu genome and the similarity between Fugu and mammalian genes. The Fugu genome, with eight times less DNA but a similar gene repertoire, is ideally suited to this type of study because most cosmids contain more than one identifiable gene. General features of the genome are also discussed. We have made some estimation of the syntenic relationship between mammals and Fugu and looked at the efficacy of ORF prediction from short, unedited Fugu genomic sequences. Comparative DNA sequence analyses are an essential tool in the functional interpretation of complex vertebrate genomes. This project highlights the utility of using the Fugu genome in this kind of study.